Robust evidence supports a causal link between higher birthweight and longer telomere length: a mendelian randomization study - Zhang, Zhuoya; Zhang, Jiale; Zhang, Kaiqi; Ge, Xiaolei; Zhai, Xu (Frontiers in Genetics, 2024)
Background Observational studies have suggested a potential relationship between birthweight and telomere length. However, the causal link between these two parameters remains undefined. In this study, we use Mendelian Randomization (MR). This method employs genetic variants as instrumental variables, to explore the existence of causal associations and elucidate the causal relationship between birth weight and telomere length. Methods We used 35 single nucleotide polymorphisms (SNPs) as instrumental variables for birth weight. These SNPs were identified from a meta-analysis involving 153,781 individuals. Furthermore, we obtained summary statistics for telomere length from a study conducted on 472,174 United Kingdom Biobank participants. To evaluate the causal estimates, we applied the random effect inverse variance weighted method (IVW) and several other MR methods, such as MR-Egger, weighted median, and MR-PRESSO, to verify the reliability of our findings. Results Our analysis supports a significant causal relationship between genetically predicted birth weight and telomer3e length. The inverse variance weighted analysis results for birth weight (Beta = 0.048; 95%CI = 0.023 to 0.073; p < 0.001) corroborate this association. Conclusion Our study provides robust evidence supporting a causal link between higher birth weight and longer telomere length.